Theory and Practice? A Comparative Analysis of Migration and Development Policies in Eleven European Countries and the European Commission. (26th March 2015) - Keijzer, Niels; Héraud, Julie; Frankenhaeuser, Malin
Abstract: This article analyses international policy discussions on migration and development (M&D) and contrasts these with the actual M&D policies and practices of 11 European countries who were among the main proponents of this international discourse. Desk research of public documents and accompanying information sought from these 11 governments as well as in the European Commission (EC) provide the basis for a comparative analysis of their overall M&D policies and strategies, and institutional settings for formulating and implementing these. The comparison shows that M&D policy and practice remains in a tentative and experimental phase, and that countries experience difficulties reflecting their international positions in their own policies, as well as in learning from their own efforts and those of others. While stressing the developmental potential of migration in international discussions, most of the countries' policies still reflect an understanding of migration as a problem and a preoccupation with short‐term domestic interests.